Teachers’ Attitudes towards Conducting Interlanguage Analysis to Prepare Better Instructions - Ruly Morganna (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2017)
This study focused on investigating attitudes had by English teachers in Indonesia towards preparing more qualified English instructions for further teaching processes through doing interlanguage analysis on the basis of students’ current competence of using English. The term competence in this study referred to students’ communicative competence. This study was conducted qualitatively to probe into the participants’ attitudes on doing interlanguage analysis, in that they were ten English teachers having been teaching English in Indonesian schools with varied experiences. They were selected purposively under considerations that they were experienced and taking graduate program, so that they were sufficiently familiar with this study issues, and it could be guaranteed that they managed to furnish the clarity of this study data. The data of this study were obtained through disseminating semi-structured questionnaire to the participants, and then pursuing the data was also undertaken to reach the clarity. The results indicated that despite some particular and situational constraints, all participants shared their positive attitude towards conducting interlanguage analysis on students’ English competence from the viewpoints of affection, behavior, and cognition. This study was essential since it could contribute on being one of references for English teachers to improve the quality of further instructions. This study was only delimited on the area of attitude. More researches were also expected to be conducted especially on the area of interlanguage analysis application to reveal more valuable and contributive knowledge in this issue.